1987
DOI: 10.7567/jjaps.26s3.1431
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Coupled Pb/Ge and Pb/C Multilayers

Abstract: We report on measurements of the dimensional crossover effect in superconducting Pb/Ge and Pb/C multilayers. The critical field data indicate the presence of a proximity effect at the interface between the Pb and the Ge or C. Using the model of Tachiki and Takahashi, we calculate the finite density of states near the Fermi-level in the Ge and C layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The 3D-2D crossover was observed experimentally for various types of superconducting multilayers having different structures such as superconductorinsulator-superconductor ͑SIS͒, e.g., Pb/C, 12 superconductorsemiconductor-superconductor, e.g., Nb/Ge, 13 superconductor-normal-metal-superconductor ͑SNS͒, e.g., Nb/Cu, [14][15][16] V/Ag, 17 and V/Cu, 18,19 superconductormagnetic-metal-superconductor ͑SMS͒, e.g., V/Ni, 20 and superconductor-superconductorЈ-superconductor ͑SSЈS͒, e.g., Nb/NbTi, 21 and Nb/NbZr, 22 and some other. In all the mentioned cases, independent of the structure of the multilayers a linear-to-square root transition in the temperature dependence of the upper critical field parallel to layers, H c2 ʈ (T), was observed, representing the 3D-2D crossover.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The 3D-2D crossover was observed experimentally for various types of superconducting multilayers having different structures such as superconductorinsulator-superconductor ͑SIS͒, e.g., Pb/C, 12 superconductorsemiconductor-superconductor, e.g., Nb/Ge, 13 superconductor-normal-metal-superconductor ͑SNS͒, e.g., Nb/Cu, [14][15][16] V/Ag, 17 and V/Cu, 18,19 superconductormagnetic-metal-superconductor ͑SMS͒, e.g., V/Ni, 20 and superconductor-superconductorЈ-superconductor ͑SSЈS͒, e.g., Nb/NbTi, 21 and Nb/NbZr, 22 and some other. In all the mentioned cases, independent of the structure of the multilayers a linear-to-square root transition in the temperature dependence of the upper critical field parallel to layers, H c2 ʈ (T), was observed, representing the 3D-2D crossover.…”
Section: Introductionmentioning
confidence: 94%
“…͑i͒ Linear-to-square root transition in H c2 ʈ (T). [12][13][14][15][16][17][18][19][20][21][22] As it follows from the LD model in the vicinity of T c , the ML behaves as a 3D anisotropic superconductor with linear temperature dependence of H c2…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the dimensional crossover in the temperature dependence of the parallel critical field was theoretically predicted [2] and experimentally observed in a number of multilayers, e.g. Nb/Cu [3],V/Ag [4],Nb/Ge [5],Pb/Ge [6].…”
Section: Introductionmentioning
confidence: 86%
“…In recent years, the structural analysis of multilayers has received considerable attention [l]. The details of the structure of the individual components and the interface are often crucial for the understanding of the superconducting [2] and magnetic [3] properties of the multilayers. It has also been shown that the structure of the interface plays a dominant role in the melting [4] or crystallisation [5] behaviour of one of the components.…”
Section: Introductionmentioning
confidence: 99%